The Role of Information Technology in Optimizing the Internal Audit Process and Improving the Quality of Internal Audit - Taufik Ridwan Hermawan; Trinandari Prasetyo Nugrahanti (Westscience Press, 2024)
This study describes the influence of the use of information technology on the quality of internal audits in Indonesia using the meta-synthesis method. The results show that the use of information technology has an important role in determining audit quality. It also highlights the importance of auditor competence in mastering various information technology tools and responding to changes that occur, especially in the business world, as well as helping auditors to carry out audit planning by monitoring the lifestyle of suspected fraudsters. This research can contribute to the development of audit practices and adaptation to technology. The implications are to help audit practitioners, regulators and stakeholders in increasing the use of information technology for better audit quality in the future. The digital era also presents challenges for auditors to be able to further improve their performance capabilities in order to adapt to future advances in information technology.